Indigo Carmine Binding to Cu(II) in Aqueous Solution and Solid State: Full Structural Characterization Using NMR, FTIR and UV/Vis Spectroscopies and DFT Calculations - Braz, Sofia; Justino, Licinia L. G.; Ramos, M. Luisa; FAUSTO, RUI (MDPI, 2024)
The food industry uses indigo carmine (IC) extensively as a blue colorant to make processed food for young children and the general population more attractive. Given that IC can act as a ligand, this raises concerns about its interactions with essential metal ions in the human body. In view of this interest, in the present investigation, the copper(II)/indigo carmine system was thoroughly investigated in aqueous solution and in the solid state, and the detailed structural characterization of the complexes formed between copper(II) and the ligand was performed using spectroscopic methods, complemented with DFT and TD-DFT calculations. NMR and UV/Vis absorption spectroscopy studies of the ligand in the presence of copper(II) show changes that clearly reveal strong complexation. The results point to the formation of complexes of 1:1, 1:2 and 2:1 Cu(II)/IC stoichiometry in aqueous solution, favored in the pH range 6-10 and stable over time. DFT calculations indicate that the coordination of the ligand to the metal occurs through the adjacent carbonyl and amine groups and that the 1:1 and the 2:1 complexes have distorted tetrahedral metal centers, while the 1:2 structure is five-coordinate with a square pyramidal geometry. FTIR results, together with EDS data and DFT calculations, established that the complex obtained in the solid state likely consists of a polymeric arrangement involving repetition of the 1:2 complex unit. These results are relevant in the context of the study of the toxicity of IC and provide crucial data for future studies of its physiological effects. Although the general population does not normally exceed the maximum recommended daily intake, young children are highly exposed to products containing IC and can easily exceed the recommended dose. It is, therefore, extremely important to understand the interactions between the dye and the various metal ions present in the human body, copper(II) being one of the most relevant due to its essential nature and, as shown in this article, the high stability of the complexes it forms with IC at physiological pH.
Keywords: Cu2+; DFT; FTIR; Indigo Carmine; Metal Complexes; NMR; UV/Vis